2021
DOI: 10.1038/s41598-021-02635-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of cervical conization with positive margins in cervical cancer

Abstract: Radical surgery after cervical conization is a common approach for the treatment of cervical cancer. In some cases, disease progression is observed after positive margins at conization, but the effect of conization on disease progression remains unclear. Thus, the aim of this study was to investigate the clinical outcomes of positive margins at conization in cervical cancer. A total of 101 patients who underwent cervical conization before radical hysterectomy and pelvic lymph node dissection were considered el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Traumatic events were life events or disasters that threatened or seriously harmed life and physical integrity, such as the death of a loved one, accident, cancer, war, and natural disaster, which often damaged the physical and mental health of individuals [14]. Cervical cancer was one of the severe traumatic events that threatened the health and life of an individual, causing great damage not only to the individual's body but also to their psychological trauma [15]. e probability of posttraumatic stress disorder among people who had suffered major trauma was as high as 58% [16].…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic events were life events or disasters that threatened or seriously harmed life and physical integrity, such as the death of a loved one, accident, cancer, war, and natural disaster, which often damaged the physical and mental health of individuals [14]. Cervical cancer was one of the severe traumatic events that threatened the health and life of an individual, causing great damage not only to the individual's body but also to their psychological trauma [15]. e probability of posttraumatic stress disorder among people who had suffered major trauma was as high as 58% [16].…”
Section: Discussionmentioning
confidence: 99%
“…Margin involvement is regarded as an important predictor of residual disease [ 5 , 14 , 26 ]. Repeated cervical conization is considered an acceptable alternative for women with a positive cone margin who desire fertility preservation, and hysterectomy is the definitive therapy for women with no reproductive requirements [ 27 , 28 ]. If the choice of treatment is new conization or hysterectomy, most women will unnecessarily undergo these procedures because they have no residual lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluated independent pre-conization variables and concluded that some pretreatment predictors might help in planning cervical conization [ 28 , 39 , 40 ]. In our study, logistic regression analysis revealed that involvement of the four quadrants was the only significant independent predictor of residual lesion.…”
Section: Discussionmentioning
confidence: 99%
“…10 Most previous studies on the prognosis of cervical cancer focused on tumour or treatment-related factors. 11,12 However, the prognostic implications of body composition remain unclear in patients with cervical cancer.…”
Section: Introductionmentioning
confidence: 99%